[OP.LB.02.04] CENTRAL ILIAC ARTERIOVENOUS ANASTOMOSIS FOR UNCONTROLLED HYPERTENSION: 12 MONTH FOLLOW UP RESULTS OF THE ROX CONTROL HTN RANDOMISED CONTROLLED TRIAL. (September 2016) - Lobo, M.; Saxena, M.; Sobotka, P.A.; Ott, C.; Dolan, E.; Foran, J.; Furniss, S.S.; Cockcroft, J.; Van Der Giet, M.; Hoyer, J.; Januszewicz, A.; Ng, G.A.; et al.
Abstract : Objective: Creation of a central iliac arteriovenous (AV) anastomosis using a novel nitinol coupler device results in an immediate, significant reduction of blood pressure (BP). We present efficacy and safety findings at 12 months post coupler insertion, extending the initial 6 month primary endpoint report (Lancet 2015). Design and method: This open-label, multicentre, prospective, randomised trial, enrolled patients with a baseline office systolic blood pressure (SBP) >140 mmHg, average daytime ambulatory SBP > 135 mmHg, and ambulatory diastolic blood pressure (DBP) > 85 mmHg. Subjects were randomly allocated to AV coupler implantation and continuing previous pharmacotherapy, or to maintain previous treatment alone. Results: Eighty-three (43%) of 195 patients screened for eligibility were randomly allocated to AV coupler therapy (n = 44) or control (n = 39) groups. At 12 months, 39 patients who had AV coupler therapy were included in the intention to treat analysis. Office-based SBP reduced by 25.1 ± 23.3 mmHg (baseline 175 ± 18 mmHg, p < 0·0001) post AV coupler placement, and office DBP reduced by 20.8 ± 13.3 mmHg (baseline 100 ± 13 mmHg, p < 0·0001). Mean 24-hour ambulatory SBP reduced by 12.6 ± 17.4 mmHg (baseline 157 ± 15 mmHg, p < 0·0001), post coupler treatment. Mean 24-hour ambulatory DBP reduced by 15.3 ± 9.7 mmHg (baseline 93 ± 11 mmHg, p < 0·0001). (see Figure). Figure. No caption available. In a pre-specified subset of patients who had failed to respond adequately to prior renal denervation, AV coupler therapy lead to highly significant reduction in office SBP/DBP (30.7/24.1 mmHg) and significant reduction in 24 hour ambulatory SBP/DBP (12.4/14.4 mmHg) at 12 months follow up. In the 12 months following randomisation, the control population has experienced a single death, attributed to hypertensive heart failure, and 6 hospitalisations in 4 patients. Following AV coupler therapy, 14 patients (33%) developed ipsilateral venous stenosis; all were treated successfully with venous stenting. Conclusions: Office and ambulatory BP were substantially and durably reduced following coupler implantation. The control population experienced both hypertension-related morbidity and mortality, not observed in the treatment group. These findings confirm the importance of arterial mechanics in the pathophysiology of hypertension and support the clinical utility of a central iliac AV anastomosis.